2008
DOI: 10.1192/bjp.bp.107.045930
|View full text |Cite
|
Sign up to set email alerts
|

Parents' perspectives on adolescent self-harm: Qualitative study

Abstract: Parents require advice and support from outside services to help them manage self-harming behaviour and its personal impact. This study suggests parents are early to spot signs of self-harm, indicating their key role in reaching young people in the community who remain unknown to health services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
172
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(185 citation statements)
references
References 14 publications
9
172
1
3
Order By: Relevance
“…Previous qualitative research has explored the needs, perspectives and responses of parents to their children's self-harm (Byrne, Morgan, Fitzpatrick et al, 2008., Oldershaw et al, 2008Raphael, Clarke & Kumar, 2006). These studies found that parents were deeply distressed by self-harm and that they struggled to understand and cope with it.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous qualitative research has explored the needs, perspectives and responses of parents to their children's self-harm (Byrne, Morgan, Fitzpatrick et al, 2008., Oldershaw et al, 2008Raphael, Clarke & Kumar, 2006). These studies found that parents were deeply distressed by self-harm and that they struggled to understand and cope with it.…”
Section: Introductionmentioning
confidence: 99%
“…Many feel that they cannot make sense of, or come to terms with, their child's self-harming behaviour (Oldershaw et al, 2008). In health research 'sense-making' has become a prominent theme in studies of chronic illnesses …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oldershaw et al, (2008) found that parents' viewed their child's self-harm as a 'phase' or as an indication 14 that they were conforming to a 'fashion'. In addition to this, it was also found that parents perceived their child's self-harming behaviours as their own choice.…”
Section: Resultsmentioning
confidence: 99%